Iowa Ornithologists' Union, Quarterly field report, fall 1992 - Kent, Thomas H. (Thomas Hugh), 1934-et al; Bendorf, Carl J.et al; Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Quarterly field report for the fall of 1992 compiled by Thomas H. Kent, James L. Fuller and Carl J. Bendorf. Plustek - flatbed